Pengaplikasian Multiple Indicator Multiple Causes (MIMIC) Model dalam Mendeteksi Differential Item Functioning (DIF) pada Alat Ukur Social Quality of Life - Hasbi Wahyudi (JP3I (Jurnal Pengukuran Psikologi dan Pendidikan Indonesia), 2019)
AbstractThis study aims to detect DIF (differential item functioning) on a quality of life measurement tool that measures one aspect, namely social quality of life. Social quality of life contains 24 items developed from the Patient Reported Outcomes Measurement Information System (PROMIS) by a National Institutes of Health (NIH). This measuring tool measures the quality of life in the social function domain of adolescent patients suffering from diseases or chronic medical conditions. Detection of DIF in this study uses a special case approach from CFA, namely CFA with covariate or multiple indicator multiple causes (MIMIC) models. This study involved 322 participants, 117 (36%) male participants and 205 (64%) female participants, with an age range between 13-23 years in Riau Province. Based on the results of the first order CFA on a set of social quality of life items there are 22 valid items. Then the MIMIC model analysis results found that the model is fit with data where the value of RMSEA = 0.048, so it is known two items that contain DIF, namely item 5 (0.135, P = 0.002) "I have a close friend" and item 23 (0.308, P = 0.002 ) "I hope to have lots of friends".Keywords: Social quality of life, MIMIC model, differential item functioningAbstrakPenelitian ini bertujuan untuk mendeteksi DIF (differential item functioning) pada alat ukur quality of life yang mengukur salah satu aspek yaitu social quality of life. Social quality of life berisi 24 item yang dikembangkan dari Patient Reported Outcomes Measurement Information System (PROMIS) oleh sebuah badan National Institutes of Health (NIH). Alaalat ukur ini mengukur kualitas hidup pada domain fungsi sosial pasien remaja yang menderita penyakit atau kondisi medis kronis. Pendeteksian DIF pada penelitian ini menggunakan pendekatan kasus khusus dari CFA, yakni CFA with covariate atau multiple indicator multiple causes (MIMIC) model. Penelitian ini melibatkan 322 partisipan, yakni sebanyak 117 (36%) partisipan laki-laki dan 205 (64%) partisipan perempuan, dengan rentang usia antara 13-23 tahun di Propinsi Riau. Berdasarkan hasil first order CFA pada sekumpulan item-item social quality of life terdapat 22 item yang valid. Kemudian hasil analisis model MIMIC ditemukan bahwa model fit dengan data dimana nilai RMSEA = 0.048, sehingga diketahui dua item yang mengandung DIF, yaitu item 5 (0.135, P = 0.002) “saya memiliki teman dekat” dan item 23 (0.308, P = 0.002) “saya berharap mempunyai banyak teman”.Kata kunci: Social quality of life, MIMIC model, differential item functioning